Exploring Efl Stuednts’ Challenges In Academic Writing: The Case Of Indonesian Higher Education - Syla Fadila Batubara; Rahmah Fithriani (Universitas Cokroaminoto Palopo, 2023)
A limited survey was conducted to evaluate the difficulities that EFL students face when writing academically. The aim of this research is to answer two questions; why Indonesian EFL students find it hard to write academically? What challenges they encountered in academic writing? the subject were ten undergraduate students of English Departmen. Questionare was used to gather the data of this study and it mostly a close-ended questions. To support the data from questionare, two subjects were asked to do interview similar to questionare. The data analysis revealed the most common difficulities students encounter is language, structure and content. Others are related to writing self-efficacy, and the least problematic is student’s lack of motivation and practice.